Intellectual property rights in India - Ahuja, V. K. (Gurgaon, 2015)
This book discusses and analyses the law on IPRS in India in a lucid language. It explains the know-how and licenses to give an overall picture of the law on IPRS.
Keywords: Intellectual property rights-India